INTERCULTURAL COMMUNICATION EFFORTS OF THE BADUY TRIBE COMMUNITY WITH TOURISTS WHO HAVE DIFFERENT CULTURES IN KANEKES VILLAGE, LEBAK DISTRICT, BANTEN - Khaeruman Khaeruman; Suflani Suflani; Rika Kartika; Pramudi Harsono; Leni Triana; Abdul Bahits (International Journal of Engagement and Empowerment, 2022)
This social service discusses cross-cultural communication between the Baduy people and tourists from different cultural backgrounds. The constant meeting of people from different cultural backgrounds affects both sides. The Baduy tribe is one of the tribes that still defends itself from the influence of modernity. They live around the Kendeng Mountains, Kanekes Village, Leuwidamar District, Lebak and Banten Regencies. Tourists from various cultural backgrounds continue to come to visit the Baduy tribe. In a long process, the Baduy tribe has adapted to a situation where their lives are closely related to travelers. However, the proximity and intercultural communication that emerged brought change to the Baduy people, whether they realized it or not. The results of community service during Baduy observation activities and interviews obtained information from outside the Baduy, the Baduy Regional Government, tourists and researchers. Cultural differences between Baduy and tourists can be considered as a fact, and verbal and non-verbal communication is a phenomenon that can be found. This phenomenon is the result of continuous and long-lasting intercultural communication. Some of the existing obstacles change the behavior of the Baduy people